Novel model and maximum power tracking algorithm for thermoelectric generators operated under constant heat flux - Compadre Torrecilla, Marcos; Montecucco, Andrea; Siviter, Jonathan; Knox, Andrew R.; Strain, Andrew (Applied energy, 2019)
•The maximum power point of a TEG under constant heat flux differs from constant ΔT.•Thermal transients impact the tracking accuracy of maximum power point algorithms.•The new proposed algorithm generates more power than other state-of-the-art methods.•The performance of the new algorithm for different heat flux profiles is shown.•Maximum power occurs when the voltage is higher than half the open-circuit voltage. Thermoelectric generators (TEGs) are solid-state devices used to convert heat into electricity. The use of TEGs in waste heat recovery systems offers a source of sustainable electricity, which helps to reduce emissions to the environment. Optimization of the electrical operating point of TEGs is important to improve the overall efficiency of TEG systems. Previous literature focused mostly on characterizing the maximum power point (MPP) of TEGs when operating at constant temperature difference. However, in most practical applications TEGs operate under constant or limited heat conditions. In fact, in waste heat recovery systems the amount of thermal energy is limited. This work presents a new simplified TEG model that simulates the dynamic response of the TEG systems with a good degree of accuracy. With the aid of this TEG model, power and control electronics have been designed to operate a TEG system, with limited input heat flux, at its optimum load. The control architecture is based on the perturb and observe maximum power point tracking (MPPT) technique and modified totake into consideration the thermal transient response of the TEG. A boost dc-dc converter is used to step-up the TEG voltage to 28 V for connection to an eight-cell Lithium-Ion battery. A microcontroller implements the control algorithm that drives the power converter. Experimental results show that the proposed algorithm outperforms two state-of-the-art algorithms (standard perturb and observe and fractional open-circuit) by 1.14% and 2.08%, respectively, when the TEG operates under constant heat flux.